1997
DOI: 10.1177/001139297045003006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Inequalities: Literature Review and Proposals for New Directions in Research and Theory

Abstract: The first battles that led to the formation of the Environmental Justice movement also produced the first studies of race and exposure to toxins. Subsequently, demographers, geographers, sociologists, political scientists, historians and legal scholars have all contributed to an ever-expanding body of studies. We review the most important works that have been published in the 1990s, focusing especially on studies of waste sites, studies of toxic industrial emissions and, finally, on local histories that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
165
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(167 citation statements)
references
References 13 publications
1
165
0
1
Order By: Relevance
“…Unfortunately, the nature of racism is not one of them. In a review of thirty recent empirical studies, only a handful attempted any substantive discussion of racism itself (Baden and Coursey, 1997;Bullard, 1990;Hamilton, 1995;Krieg, 1995;Pulido et al, 1996;UCC, 1987) 7 , although others have probed the nature of race and racism in general (Bullard, 1994;Goldman, 1996;Pulido, 1996;Szasz and Meuser, 1997;Zimmerman, 1994). Instead, the literature is largely characterized by "common sense" assumptions that reflect uncritical, popular understandings of racism 8 .…”
Section: Racism and Space In Environmental Racism Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the nature of racism is not one of them. In a review of thirty recent empirical studies, only a handful attempted any substantive discussion of racism itself (Baden and Coursey, 1997;Bullard, 1990;Hamilton, 1995;Krieg, 1995;Pulido et al, 1996;UCC, 1987) 7 , although others have probed the nature of race and racism in general (Bullard, 1994;Goldman, 1996;Pulido, 1996;Szasz and Meuser, 1997;Zimmerman, 1994). Instead, the literature is largely characterized by "common sense" assumptions that reflect uncritical, popular understandings of racism 8 .…”
Section: Racism and Space In Environmental Racism Researchmentioning
confidence: 99%
“…White privilege, together with overt and institutionalized racism, reveals how racism shapes places. Hence, instead of asking if an incinerator was placed in a Latino community because the owner was prejudiced, I ask, why is it that whites are not comparably burdened with pollution (see Szasz and Meuser, 1997)? In the case of Los Angeles, industrialization, decentralization, and residential segregation are keys to this puzzle.…”
mentioning
confidence: 99%
“…Since then, a steadily increasing number of researchers have investigated the relationship between neighbourhood demographic composition and environmental hazard presence (Szasz and Meuser, 1997;Bowen, 2002). However, relatively few researchers have attempted to determine why the distribution of social groups around environmental hazards takes the form that it does or why some studies have found strong evidence of environmental racial inequality while others have not Weinberg, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A third possible explanation is that studies vary according to the region and type of region (i.e. rural vs urban) examined (Brown et al, 1997;Clark et al, 1995;Szasz and Meuser, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although environmental inequalities persisted historically (Taylor 1997;, environmental justice was not utilized as an organizing concept until the 1980s, when African American communities, black scholars, and the progressive United Church of Christ began to draw attention to environmental inequities experienced in black communities (Mohai, Pellow, and Roberts 2009;Szasz and Meuser 1997). Developing shortly after the civil rights movement, Everett Parker and Robert Bullard pursued environmental injustice narratives around civil rights and the experiences of African Americans in the southern United States, which were largely left out of mainstream environmental movements (generally white, male, wealthy; see Taylor 2000).…”
Section: Environmental Justice: Origins Conceptualizations and Advamentioning
confidence: 99%